Durability response of a cemented clayey sand over a wide range of porosities and cement contents - Hugo Carlos Scheuermann Filho; Gustavo Dias Miguel; Nilo Cesar Consoli (Cleaner Materials, 2022)
The adjusted porosity/cement index η/(Civ)a has proven to be a powerful tool related to the dosage of soil–cement mixtures as it encompasses into a unique parameter the effect of either the cement content and the compactness on the mechanical response (e.g. strength, stiffness and durability) of such materials. Theoretically, by setting a specific η/(Civ)a value, a very similar mechanical response should be obtained by the use of distinct dosages assembled through the combinations of a variety of porosities and amounts of cement. In this regard, the most environmental attractive dosage can be chosen considering a specific construction case. Yet, such possibility has not yet been evaluated, specifically, for the durability tests. Thus, present study aspires to address this lacuna by carrying out these tests via wetting–drying-brushing cycles on different dosages established within five η/(Civ)0.28 values (i.e., 45, 30, 35, 25, and 20). Two different mix designs were assembled within each η/(Civ)0.28 for compacted clayey sand-cement blends, being the results statistically evaluated aiming to check for the equivalence of the attained results. In addition, the accumulated loss of mass data was successfully correlated to the η/(Civ)0.28 index through power-type relationships.